The Effect of Morinda citrifolia L. Fruit Extract Supplemented in to Diluent Tris-Egg Yolk Toward the Abnormality of Goat's Spermatozoa after Freezing at -80°C - Rophi, Apriani Herni; Rahayu, Sri; Ciptadi, Gatot (The Journal of Experimental Life Science, 2018)
The aim of this research is to know the effect of diluent Tris-egg yolk medium added with Morinda citrifolia L. extract towards the sperms abnormality after storage at -80°C for 24 hours. The extracts added in diluent Tris-egg yolk medium were 0% (P0), 10% (P1), 20% (P2), and 30% (P3). The result showed that the percentage of sperms abnormality in P0, P1, P2, and P3 were respectively 8.67%, 6.67%, 5.67%, and 10%. P2 was the lowest percentage, while P3 was the highest percentage of sperms abnormality. In addition, this research found twelve kinds of sperms abnormality divided into categories: major abnormality included the broke tail, absent head, detached head, dag defect, tapered head, proximal droplet, round head and abaxial; and minor abnormality included the coiled tail, shoe hook tail, bent tail, and distal droplet. It has been concluded that the allotment of 20% Morinda citrifolia L. extracts in Tris-egg yolk medium able to maintain the sperm morphology at -80°C storage for 24 hours. Keywords: goat, Morinda citrifolia L., post-thawing, spermatozoa.